2018
DOI: 10.31025/2611-4135/2018.13641
|View full text |Cite
|
Sign up to set email alerts
|

Waste Management in Remote Rural Communities Across the Canadian North: Challenges and Opportunities

Abstract: We report results from a two-phase mixed methods research study to illustrate challenges and opportunities of waste management within the rural circumpolar and boreal regions of Canada. In the qualitative research phase, data were obtained from archives, semi-structured interviews with community partners, an information meeting with a community grassroots organization, and a participatory action meeting to develop a case study of the Labrador waste management system. Like many regions across the world's boreal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The breakeven, sensitivity, and stochastic analyses presented in this paper expand upon an Excel‐based enterprise budget previously developed for a prospective biochar production project colocated at the Muskrat Falls hydroelectric mega‐project site (Keske, Mills, Godfrey, Tanguay, & Dicker, ), which is slated to begin energy production in late 2019 or early 2020. In that article, the authors postulated that biochar and agricultural coproduction, incorporating biochar as a soil amendment, show potential as a profitable venture, which motivated the presenting research study.…”
Section: Methodsmentioning
confidence: 99%
“…The breakeven, sensitivity, and stochastic analyses presented in this paper expand upon an Excel‐based enterprise budget previously developed for a prospective biochar production project colocated at the Muskrat Falls hydroelectric mega‐project site (Keske, Mills, Godfrey, Tanguay, & Dicker, ), which is slated to begin energy production in late 2019 or early 2020. In that article, the authors postulated that biochar and agricultural coproduction, incorporating biochar as a soil amendment, show potential as a profitable venture, which motivated the presenting research study.…”
Section: Methodsmentioning
confidence: 99%
“…These concerns have been articulated by Bharadwaj et al (2006) and Schiff & Bernard (2018) as overarching issues within First Nations communities across Canada, which rely upon hunting and gathering country foods for their sustenance. For more discussion about country foods among First Nations communities across Canada, and in relation to Newfoundland and Labrador's population as a whole, please consult Van Oostdam et al (1999) and Keske (2018), respectively. This is exacerbated by the lack of organic waste diversion since, on account of the cold climate, permafrost, and poor soils, composting for agriculture is not a major strategy.…”
Section: Results From Nain: Waste Management In Remote Self-containementioning
confidence: 99%
“…Results from the qualitative phase were used to identify potential waste streams for a quantitative data analysis on the economic feasibility of a sustainable waste management solution within the study region. Results from the quantitative phase are available in Keske, Mills, Godfrey, Tanguay, & Dicker (2018).…”
Section: Literature Review On Northern Waste and Mixed Methods Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that incomplete disposal of wastes in the natural areas affects all animals (2,6,7). Some studies also indicated that some of the environmental problems caused by waste on animal habitats are soil pollution, water pollution, disease and death of wildlife (8). Ye and Qin evaluated the status of rural waste management in China.…”
Section: Introductionmentioning
confidence: 99%